Stability of novel urinary biomarkers used for lupus nephritis - Cody, Ellen M.; Rose, James E.; Huang, Bin; Qiu, Tingting; Brunner, Hermine I.; Devarajan, Prasad (Frontiers in Pediatrics, 2022)
Background The Renal Activity Index for Lupus (RAIL) is a composite score of six urinary biomarkers (neutrophil gelatinase–associated lipocalin (NGAL), monocyte chemoattractant protein-1 (MCP-1), kidney injury molecule-1 (KIM-1), ceruloplasmin, adiponectin, and hemopexin) used to monitor lupus nephritis activity in children. We tested stability of RAIL biomarkers prior to meaningful clinical use. Methods Urine samples were tested by ELISA under shipping conditions, freeze/thaw, ambient and longer-term storage. Statistical analysis was performed via Deming Regression, Bland-Altman and Spearman Correlation Coefficient. Results Biomarker concentration were comparable to freshly collected urine following storage at −80 °C for up to 3 months, and at 4 or 25 °C up to 48 h followed by −80 °C. Neither shipping on dry or wet ice exposure nor addition of two freeze-thaw cycles led to loss of signal, with excellent Spearman Correlation coefficients under all conditions. Conclusions RAIL biomarkers are stable following short-term storage at clinically relevant conditions.